Impact of high temperature stress during reproductive and grain filling stage in rice - R, Beena; Vighneswaran, Veena; P, Sindhumole; Narayankutty, M C; Voleti, S R (ORYZA-An International Journal of Rice, 2018)
Pot experiment was conducted at R.A.R.S., Pattambi, Kerala Agricultural University during Kharif, 2013. The main objective of the experiment was to study the effect of high temperature on physiological traits and spikelet fertility in rice genotypes. The treatment consisted of 29 rice genotypes with two temperature treatments. The experiment was laid out in completely randomized design (CRD) replicated three times. Plants were raised in earthern pots under ambient condition. High temperature treatment was induced from panicle initiation to maturity. At the time of panicle initiation, one set of plants were shifted to a polyhouse and exposed to high temperature (6-8Â°C above the ambient condition) until maturity. The result indicated that high temperature significantly reduced the spikelet fertility percentage in all genotypes except N-22. Among the other varieties, Jyothi showed less reduction in spikelet fertility with an average photosynthetic rate under stress condition. Days to 50% flowering was advanced by 2-7 days in stress treatment. Photosynthetic rate and SPAD chlorophyll meter reading were reduced significantly under high temperature condition. Specific Leaf Area (SLA), Canopy temperature, stomatal conductance and transpiration rate were increased under stress treatment.